Pengelolaan Bisnis Secara Islami Sebagai Aspirasi Mahabbah Al-Rasul: Telaah Kitab Nurul Mubin - Choiriyah, Siti Khusnatul; Sopingi, Imam; Hidayati, Athi’ (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2025)
The scope of this study contains Islamic business management as a concrete manifestation of maḥabbah (love) for the Prophet Muhammad SAW by examining the book Nurul Mubin by KH. Hasyim Asy'ari. This study aims to reveal how the values of Islamic business ethics derived from the morals of the Prophet Muhammad SAW can be implemented in the modern business world. The research uses a descriptive qualitative method with a literature study approach. Data were collected through analysis of relevant literature, particularly Kitab Nurul Mubin, to identify central values such as honesty (ṣidq), justice ('adl), trustworthiness, as well as the prohibition against usury, gharar, and fraud. The results show that business management based on the Prophet's moral values not only strengthens moral and spiritual foundations, but also becomes a practical strategy in building business sustainability. In conclusion, maḥabbah al-Rasul can be realized in business activities by following the ethics and integrity exemplified by the Prophet Muhammad, which has a positive impact not only on business success, but also on society at large. This study encourages business actors to make love for the Prophet as an inspiration in building an ethical and civilized business system.